Hybrid Aesthetics and Cultural Politics in Chinese American and American-Influenced Music - Xing, Zijie (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Music.; Advisor: Frank Lehman.; Committee: Alessandra Campana, and Joseph Auner.; Keyword: Music.